GLANCING INDIA’S AGRICULTURAL EXPORT CONTRIBUTION DURING THE PANDEMIC PERIOD - Dr. Felice Joy (International Journal of Modern Agriculture, 2021)
The study objective was to make a comparative analysis of India’s agricultural export during and before the pandemic period. Further to identify a forecasting model to determine India’s agricultural export during the pandemic period and regular period. For the study, the analytical research design was adopted. The data was collected from APEDA (The Agricultural and Processed Food Products Export Development Authority) between the time frame of July 2019 – November 2020. Herein July 2019 -February 2020 is considered Pre-Pandemic Period and March 2020 – November 2020 is considered Pandemic Period. From the analysis performed, it is well perceived that there is a significant difference in agricultural export in terms of Quantity and Price Duringthe Pandemic Period and Pre-Pandemic Period. The calculated mean value of agricultural export in terms of quantity at the time of Pre-Pandemic period was 1372085.938 M.T., similarly, agricultural export in terms of quantity during the pandemic was 2121491.429 M.T. This indicates, India has exported high quantity of agricultural products during pandemic time than Pre-Pandemic time. Also, the calculated mean value of agricultural export in terms of price at the time of Pre-Pandemic period was 9198.932 CroreRs., similarly agricultural export in terms of price during the pandemic was 11158.029 CroreRs. This indicates India has exported agricultural products at a high price during pandemic time than Pre-Pandemic time. The forecasting equation governing the agricultural export during regular time: Agriculture Export in Rs (Crore) = -179446.944 + [168.664× Agriculture Export in QT (MT)]. Similarly, the forecasting equation governing the agricultural export during the pandemic time: Agriculture Export in Rs (Crore) = -364313.438 + [222.782× Agriculture Export in QT (MT)]